ANALISIS KONSISTENSI BETA SAHAM DI JAKARTA ISLAMIC INDEKS (JII) PERIODE 2007-2010 - Irma Mbae (Ekomen, 2013)
The sampling technique used in this research is purposive sampling with criteria such as those companies listed at JII (Jakarta Islamic Indeks) during periode of 2007 – 2010 and companies that consistently listed at JII period of 2007 – 2010 and in accordance with syariah requirements. The data is obtained based on the publication of JII during 2007 – 2010 and e-trading company. The analysis technique is a regression model that uses time as the variable and compared it with the regression model. Single indeks is used to calcute the beta.The result shows that beta stock of Jakarta Islamic Indeks (JII) relatively stable. Test of Anova model of beta stock listed at JII during period of 2007 – 2010 is not significant or in other words, the beta is stable. Test of regression model with time as a variabel shows that beta stock of companies listed at JII period of 2007-2010 is not significant or beta is stable. Test of dummy variable of beta stock is stable. Test of each company uses regression model shows that there are five company have stable beta stock since coefficient B2 is not significant, meanwhile, there are two companies have ustable beta stock because coefficient B2 is significant.Keywords : beta of stock, regression model, anova model and dummy variabel method.